Concept and Design of a Virtual Library - Sharma, Devendra Kumar; Bhagat, Pankaj (International Journal of Psychosocial Rehabilitation, 2020)
Libraries are centers for social and scholarly collaborations in networks and associations. Virtual libraries should fill a similar need, yet virtual libraries regularly center essentially around making their property accessible. In this article, an online corporate library is depicted that places information sharing and the network is working at the center of its structure. The library system supports personal websites that are visible to the entire organization. In this investigation of the virtual library and the job it plays for established researchers as an educational and logical specialized article, a hypothetical interdisciplinary examination was gotten together with an observational system. Old fashioned reports, which without a doubt speak to our social legacy and can be viewed as an extremely rich wellspring of data, are kept in numerous nations just on libraries with authentic chronicles. The artefact and delicacy of such archives make their entrance confined. Taking into account that nowadays the Internet is one of the most fascinating spots to distribute any sort of data, it appears to be consistent to utilize it to both save our social legacy and give more extensive access to these records.